Peran Guru sebagai Teladan (Modeling the Way) dalam Pembentukan Karakter Siswa Madrasah Ibtidaiyah - Mahtumah Mahtumah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2023)
Character building is one of the most crucial aspects in supporting national development in the current era of globalization. Education is not only intended to transfer knowledge, but also plays a role in shaping the personality and moral values of students from an early age. This is important so that students have a strong character provision to face the challenges of the ever-changing era. Instilling character values from an early age is expected to be a fortress in maintaining students' personal and social integrity. The purpose of this study is to determine and describe the role of teachers as role models (modeling the way) in the process of character building for students in the Elementary Madrasah environment. The approach used in this study is a qualitative approach with a descriptive research type. Data collection techniques are carried out through direct observation in the field and in-depth interviews with teachers, principals, and students involved in learning activities. This research was conducted in an Elementary Madrasah that has implemented an exemplary approach in the character education process. The results of the study indicate that the role of teachers as role models is very influential in shaping the character of students. The attitudes, words, and actions of teachers in everyday life in the madrasah environment are real examples that are imitated by students. Thus, it can be concluded that the modeling the way strategy is very effective in internalizing character values to students at the Madrasah Ibtidaiyah level.